Referential Semantics of Coastal Toponyms: A Case Study Central Java - Zulfa, Ilma; Hendrokumoro, Hendrokumoro (Journal of Language and Literature Studies, 2025)
Toponymy is a branch of linguistics that examines the interrelationship between language, culture, and environment through place naming. In coastal regions, place names often reflect geographical features, natural elements, and community perceptions of their surroundings. This study aims to uncover the referential meanings embedded in coastal toponyms by employing a referential semantics approach. The analysis interprets the relationship between the linguistic form of each toponym and its real-world referent, while classifying naming motivations using the Australian National Placenames Survey (ANPS) typology. The findings reveal that referential meanings predominantly represent denotative and ecological relations, indicating that coastal toponyms are grounded in physical and environmental features. This is evident from the dominance of the Descriptive category (50.0%), followed by the Associative (20.5%) and Evaluative (15.9%) categories. These categories reflect not only geographical and ecological characteristics but also cultural associations and value-laden expressions embedded in naming practices. Beyond its theoretical contribution, this study offers practical implications for cultural heritage preservation. The analysis of semantic motivations behind place naming can serve as a linguistic foundation for documenting traditional toponyms, supporting local government efforts to standardize and preserve place names, and strengthening intangible cultural heritage initiatives in coastal communities. The findings also highlight the need to safeguard environmentally based toponyms that encode ecological knowledge, particularly in areas undergoing environmental change and urban development.